Preparation method of fly ash-graphite tailing / ultrafine powder based geopolymer

By chemically superfine the graphite tailings and mixing them with fly ash and cement, combined with alkali exciter solution with moderate modulus for excitation, the problem of alkali whitening of graphite tailings when preparing the ground polymer is solved, and the early strength and density of the material are significantly improved.

CN119822653APending Publication Date: 2025-04-15ENERGY & ENVIRONMENT RES INST OF HEILONGJIANG PROVINCE
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411942877.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In the prior art, when preparing the ground polymer, the modulus of the alkali exciter is small, resulting in the problem of alkali whitening and affecting the density and mechanical properties of the material.

Method used

By chemically superfine the graphite tailings, the specific surface area is improved, the porous structure is formed, and it has good dispersion properties, and mixed with low-calcium fly ash and/or cement, it is excitated using an alkali exciter solution with a modulus of 1.6 to 2.2.

Benefits of technology

It significantly improves the activity of graphite tailings, improves the early strength of the earth polymer and the denseness of microstructure, solves the problem of alkaline whitening, and enhances the compressive and flexural strength of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure HDA0005212948450000011
    Figure HDA0005212948450000011
Patent Text Reader

Abstract

The invention provides a preparation method of a geopolymer, which is characterized in that fly ash and graphite tailings are used as raw materials, and the weight ratio of the fly ash to the graphite tailings is 4: (0.25-1); or fly ash, graphite tailings and graphite tailing ultrafine powder are used as raw materials, and the mass ratio of the fly ash to the graphite tailings to the graphite tailing ultrafine powder is 4: 0.25: 0.75; the preparation method comprises the following steps: uniformly mixing the raw materials, adding an alkali activator solution, stirring for 2-4 minutes, molding, and maintaining for 28 days to obtain the geopolymer based on the solid waste. According to the method disclosed by the invention, the graphite tailing ultrafine powder is added in the preparation of the geopolymer, can provide a crystal phase for the geopolymer, and is used as aggregation functional particles, so that the microstructure of the product is more compact, and the early compressive strength of the geopolymer is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a green low-carbon gelling material, in particular to a fly ash-graphite tailings / ultrafine powder-based polymer, and a preparation method and application thereof, belonging to the field of solid waste material utilization. Background Art

[0002] Cement is a common adhesive for building materials. Its production process emits a large amount of carbon dioxide (CO 2 ). The cement industry cannot achieve significant CO reduction using existing conventional production methods and technologies. 2 Therefore, developing or creating alternative cement binders to reduce CO 2 To reduce CO2 emissions, it is imperative to improve the sustainability of building materials. Developing green and sustainable cementitious materials from a large amount of industrial solid wastes (ISWs) will not only help reduce CO2 emissions, but also help recycle environmentally harmful industrial wastes. Geopolymer is a green and low-carbon cementitious material with a three-dimensional network structure, which is polymerized by raw materials rich in silicon and aluminum under alkali activation. It is considered to be a substitute for ordinary Portland cement (OPC) and can greatly reduce CO2 emissions. 2 emissions, and increase the use of ISWs.

[0003] Graphite tailings are a type of industrial solid waste discharged during the graphite beneficiation and impurity removal process. According to statistics, during the flotation mining process, 10-15 tons of graphite tailings can be produced for every ton of graphite purified. If graphite tailings are not properly handled, it will cause serious harm to the ecological environment such as soil, water, and atmosphere, and there is also a risk of geological disasters, which will also cause waste of resources. From the perspective of chemical composition, graphite tailings mainly contain SiO 2 、Al 2 O 3 and Fe 2 O 3 Other metal oxides, including SiO 2 The content is about 58% to 64%, which is similar to fly ash. From the perspective of mineral phase structure, graphite tailings mainly contain quartz phase, plagioclase, mica and hematite. Therefore, it has the potential to replace siliceous raw materials in the field of building materials (such as low-carbon cementitious materials, geopolymers, moisture-proof, anti-corrosion and flame-retardant materials, etc.). However, the volcanic ash activity of plagioclase and quartz phases in graphite tailings is relatively low, and it is necessary to use certain technical means and process methods to effectively stimulate their activity.

[0004] In the prior art, patent document CN 118459132 A discloses a method for preparing geopolymers using graphite tailings and metakaolin. Although solid waste graphite tailings are used as silicon and aluminum sources in this method, they are excited together with metakaolin through an alkaline activator composed of water glass and sodium hydroxide to prepare geopolymers, but the modulus of the alkaline activator used when achieving good strength is small (1.0), that is, more NaOH needs to be added during configuration, and the stronger the alkalinity, the easier it is to produce alkali whitening problems. Alkali whitening of geopolymers not only affects the appearance quality, but long-term alkali whitening will also cause the internal structure of geopolymers to be loose, destroy the compactness of geopolymers, reduce their mechanical properties, thereby affecting the surface wear resistance and compressive resistance, and shortening the service life. When applied to concrete structures, the alkali problem will also accelerate the corrosion of steel bars and affect the safety of the structure. Therefore, the application value of graphite tailings in resource utilization is insufficient.

[0005] In order to further improve the resource utilization value of industrial solid wastes such as graphite tailings and fly ash and prepare geopolymers with better performance, it is necessary to propose a new method for preparing industrial solid waste-based polymers. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing geopolymers using fly ash and graphite tailings, by chemically ultrafinely treating the graphite tailings to increase its specific surface area, form a porous structure, and have good dispersibility, and mix it with low-calcium fly ash and / or cement to prepare a green and low-carbon gelling material with ideal performance.

[0007] The technical scheme of the present invention to achieve the above-mentioned purpose is as follows:

[0008] In a first aspect, the present invention provides a method for preparing a geopolymer, which uses fly ash and graphite tailings or fly ash and graphite tailings and their ultrafine powders as raw materials. After the raw materials are evenly mixed, an alkaline activator solution is added and stirred for 2 to 4 minutes. After molding and curing for 28 days, a solid waste-based geopolymer is obtained.

[0009] In the preparation method of the present invention, the fly ash is an existing product from a pulverized coal furnace in a power plant; the preferred fly ash is spherical fly ash; further preferred is low-calcium Class F secondary fly ash, which has the following components: SiO 2 Content 66%~68%, Al 2 O 3 The content is 17% to 18%, the CaO content is 4% to 6%, and the Fe 2 O 3 Content 4%~4.5%, SO 3 Content 0.2%~0.3%.

[0010] In the preparation method of the present invention, the graphite tailings are graphite tailings after calcination and activation; in the preferred graphite tailings, SiO 2 The content is between 35% and 65%, and SiO 2 and Al 2 O 3 The content ratio is between 2-5.

[0011] In the preparation method of the present invention, the graphite tailings ultrafine powder is an ultrafine powder obtained by chemical ultrafine treatment of graphite tailings particles, specifically, the ultrafine powder with a microscopic morphology of spherical or cubic is obtained by grinding the calcined activated graphite tailings particles with NaOH fine powder, and then performing high-temperature roasting, grinding, low-temperature aging and hydrothermal reaction in sequence; in the graphite tailings ultrafine powder, more than 90% of the particles have a particle size of no more than 20 μm; the micropore area is no less than 30 m 2 / g; specific surface area not less than 19m 2 / g.

[0012] In the preferred preparation method of the present invention, the ultrafine graphite tailings powder is prepared according to the following method:

[0013] 1) mixing sodium hydroxide (NaOH) fine powder with calcined activated graphite tailing particles in a weight ratio of 0.6 to 2.0:1 and grinding them together until they are completely mixed and then roasting them at 650° C. to 750° C. for 2 h to 4 h;

[0014] 2) mixing the solid treated in step 1) with sodium silicate at a weight ratio of 1:0.30-0.80 and grinding them into powder, then adding water at a solid-liquid ratio of 6-12 mL / g, first aging at 50-80° C. for 1 h-3 h, and then aging at room temperature for 12 h-16 h to obtain a precursor for a hydrothermal reaction;

[0015] 3) subjecting the precursor obtained in step 2) to a hydrothermal reaction at 95° C. to 110° C. for 7 h to 9 h, followed by cooling, filtering and drying to obtain the ultrafine graphite tailings powder used in the preparation method of the present invention.

[0016] In the preparation method of the present invention, the mass ratio of fly ash, graphite tailings and ultrafine graphite tailings powder in the raw materials is 4:0.25:0.75. Under this ratio, the early strength and microstructure of the obtained geopolymer are optimal. Therefore, this raw material ratio is the most preferred.

[0017] In the preparation method described in the present invention, the alkaline activator solution is a water glass solution with a modulus of 1.6 to 2.2. The water glass solution with this modulus can be prepared in a variety of ways, for example, a certain mass of sodium hydroxide (NaOH) particles can be added to the water glass to obtain it. The viscosity of the alkaline activator with this modulus is moderate, which can enable the geopolymer gelling material to achieve the best results in terms of fluidity and setting time, so that the best excitation effect can be obtained. In addition, when the liquid-to-gel ratio of the added alkaline activator solution is 0.35 to 0.44 and the proportion of the alkaline activator solution in the system liquid is 20% to 50%, the geopolymer can obtain better fluidity and strength.

[0018] In a second aspect, the present invention also provides another method for preparing a geopolymer, which uses fly ash, graphite tailings, ultrafine graphite tailings powder and cement as raw materials. After the raw materials are evenly mixed, an alkaline activator solution is added and stirred for 2 to 4 minutes. After molding and curing for 28 days, another solid waste-based geopolymer is obtained.

[0019] In the preparation method described in the second aspect of the present invention, the definitions of fly ash, graphite tailings and ultrafine graphite tailings powder are the same as those in the first aspect.

[0020] In the preparation method described in the second aspect of the present invention, the cement is used to further increase the strength of the geopolymer to meet the application needs of usage scenarios with higher strength requirements.

[0021] In the preparation method described in the second aspect of the present invention, the mass ratio of fly ash, graphite tailings, ultrafine graphite tailings powder and cement in the raw materials is 4:0.25:0.75:5. Under this ratio, the early strength and microstructure of the obtained geopolymer are optimal. Therefore, this raw material ratio is the most preferred.

[0022] In the preparation method described in the second aspect of the present invention, when the liquid-to-gel ratio of the added alkali activator solution is 0.35-0.44 and the proportion of the alkali activator solution in the system liquid is 20%-50%, the geopolymer can obtain better fluidity and strength.

[0023] In the present invention, the discarded graphite tailings are used as silicon and aluminum sources to prepare ultrafine powders, and the powders are blended with fly ash and graphite tailings sand, and green low-carbon gelling materials are prepared under the action of an alkali activator at room temperature, which can be used as an important new way to realize the comprehensive utilization of solid wastes such as graphite tailings. In the present invention, the ultrafine treated mineral powder (i.e., ultrafine graphite tailings powder) has the advantages of good dispersibility, filling pore structure, strengthening system mass transfer and heat transfer, and promoting boundary nucleation and precursor growth. Adding the ultrafine graphite tailings powder of the present invention in the preparation process of geopolymers or low-carbon gelling materials helps to increase the specific surface area of ​​particles in the reactant system, improve the solubility of silicon and aluminum components in the raw materials and the volcanic ash activity, and make it easier to convert the raw materials into efficient aluminosilicate materials, thereby promoting the polymerization reaction process of low-carbon gelling materials or geopolymers and enhancing their matrix structure.

[0024] The mineral phase structures of quartz, mullite and other materials in graphite tailings are very stable and difficult to dissolve when geopolymerization occurs at room temperature. In order to solve this problem, when preparing geopolymers, the activity of graphite tailings is first stimulated by mechanical grinding, acid-base excitation, high-temperature calcination and the like, and then it is blended with calcined activated graphite tailing particles, fly ash and cement and then stimulated by alkaline activator solution, thereby significantly improving the activity of graphite tailings as solid waste, and bringing about a significant improvement in the early strength of the prepared geopolymer.

[0025] Specifically, in the preparation method of the present invention, the ultrafine graphite tailings powder plays the following important roles in the geopolymerization process:

[0026] First, after being treated by chemical ultrafine processing, the particle size of the graphite tailings ultrafine powder is highly uniform, which plays a vital role in improving the compressive strength of the geopolymer. Compared with the graphite tailings raw material that has not been treated by chemical ultrafine processing, the average particle size of the graphite tailings ultrafine powder after chemical ultrafine processing is greatly reduced, reaching a level close to the average particle size of fly ash (as shown in Table 1). Under the same mass, the contact area between the liquid and the particles with smaller average size is larger, resulting in faster heat release. Therefore, the geopolymer with the graphite tailings ultrafine powder added to the raw material has a larger cumulative heat release in the initial reaction stage. Under this environment, the Si, Al, and Ca monomers or ions dissolved from the raw materials are more likely to quickly repolymerize and condense around the microsphere particles to form a gel. Therefore, more hydration and geopolymer products accumulate around the graphite tailings ultrafine powder, such as Figure 1 shown.

[0027] Second, after adding ultrafine graphite tailings powder to the raw material system, during the geopolymer reaction process, the particles agglomerate to form a gel pore structure of <10nm, which plays a micro-aggregate effect and plays a beneficial role in improving the early compressive strength and flexural strength. Figure 2 , Figure 3 shown.

[0028] In summary, the present invention provides a new idea of ​​adding ultrafine mineral powder in the preparation of geopolymers, which can provide a crystalline phase for geopolymers and serve as aggregation functional particles to make the microstructure of the product more compact and improve the early compressive strength of geopolymers. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This shows that more hydration and geopolymerization products are accumulated around the ultrafine graphite tailings powder in the geopolymer microstructure of the present invention.

[0030] Figure 2 It is a comparison chart of the compressive strength of Examples 1 to 3 and Comparative Example 1.

[0031] Figure 3 It is a comparison chart of the flexural strength of Examples 1 to 3 and Comparative Example 1.

[0032] Figure 4 It is a process flow chart of a specific embodiment of the present invention.

[0033] Figure 5 This is the fly ash-graphite tailings base polymer sample prepared in Example 1 and its microscopic morphology.

[0034] Figure 6 This is the fly ash-graphite tailings-ultrafine powder base polymer sample and microscopic morphology prepared in Example 2.

[0035] Figure 7 This is a microscopic morphology of the geopolymer prepared by the method of Comparative Example 2.

[0036] Figure 8 This is a microscopic morphology of the geopolymer prepared by the method of Comparative Example 3. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is further illustrated by describing specific implementation methods below.

[0038] The present invention provides a method for preparing a geopolymer based on solid waste, using fly ash and graphite tailings as raw materials, or a mixture of fly ash, graphite tailings and ultrafine graphite tailings powder as raw materials, so it can also be called a method for preparing a fly ash-graphite tailings / ultrafine powder-based polymer, such as Figure 4 As shown, the following steps are included:

[0039] 1) First, add a certain mass of sodium hydroxide (NaOH) particles into water glass, adjust the modulus of the water glass solution (i.e., alkali activator), stir evenly, cool to room temperature, and put into a sealed alkali-resistant container. After standing for 24 hours, prepare the alkali activator solution according to a certain liquid-to-gel mass ratio;

[0040] 2) mixing a certain proportion of powdered fly ash, graphite tailings and / or ultrafine graphite tailings powder (micro powder) and cement together, adding half of the alkali activator solution prepared in step 1) to the mixture, mixing and stirring with a stirrer and adding the remaining half of the alkali activator solution during the process, and stopping stirring after a period of time;

[0041] The graphite tailings are graphite tailings (i.e. Figure 4 GT-C750 or graphite tailings-C750); the graphite tailings ultrafine powder (micro powder) is the graphite tailings (i.e. Figure 4 GT-C750) as follows Figure 4 The method shown in the left part of the middle is chemically ultrafine and prepared by the following method:

[0042] a) mixing sodium hydroxide (NaOH) fine powder with calcined activated graphite tailing particles in a weight ratio of 0.6 to 2.0:1 and grinding them together until they are completely mixed to obtain a micro powder precursor, and then calcining at 650° C. to 750° C. for 2 h to 4 h to complete alkali fusion;

[0043] b) mixing the solid treated in step a) with sodium silicate at a weight ratio of 1:0.30-0.80 and grinding them into powder, then adding water at a solid-liquid ratio of 6-12 mL / g, first aging at 50-80° C. for 1 h to 3 h, and then aging at room temperature for 12 h to 16 h to obtain a precursor for a hydrothermal reaction;

[0044] c) subjecting the precursor obtained in step b) to a hydrothermal reaction at 95° C. to 110° C. for 7 h to 9 h, followed by cooling, filtering and drying to obtain ultrafine graphite tailings powder (micro powder).

[0045] 3) Pour the slurry obtained in step 2) into a 40 mm × 40 mm × 160 mm triple stainless steel mold, scrape the surface flat, vibrate on a vibration table to expel bubbles, and cover with a plastic cover;

[0046] 4) Place the mold containing the slurry in a constant temperature and humidity curing box, and demould after curing for 24 hours to obtain a geopolymer test block. Place the demoulded test block in a curing box filled with distilled water and continue curing until the curing is completed at 28 days. During this period, test the compressive strength of the test block at 3d, 7d, and 28d.

[0047] In the scheme of the present invention, in order to recycle industrial solid waste, step 2) selects graphite tailings produced in Luobei County, Hegang City as raw materials. 2 The content is 53% to 60%, Al 2 O 3The content is 11% to 13%, SiO 2 and Al 2 O 3 The content ratio is about 4.6-4.9, the CaO content is 8%-10%, and the Fe 2 O 3 The content is about 7% to 11%, SO 3 The content of SiO is about 2% to 6%, and the content of MgO is 1.7% to 4%. The spherical fly ash produced by the pulverized coal furnace of a power plant in Harbin was selected, and its composition is: SiO 2 Content 66%~68%, Al 2 O 3 The content is 17% to 18%, the CaO content is 4% to 6%, and the Fe 2 O 3 Content 4%~4.5%, SO 3 The content is 0.2% to 0.3%, which belongs to the low-calcium Class F secondary fly ash with low hydration heat.

[0048] In a preferred embodiment of the present invention, the modulus of the water glass solution is 1.6 to 2.2; the liquid-to-gel ratio is 0.35 to 0.44, and the proportion of the alkali activator in the system liquid is 20% to 50%.

[0049] In a preferred embodiment of the present invention, in the powder raw material, the weight ratio of (fly ash): (graphite tailings) or (a mixture of graphite tailings and ultrafine graphite tailings powder): cement is 4:1:5.

[0050] In a preferred embodiment of the present invention, the stirring time is 2 to 4 minutes, and the vibration time is 2 to 4 minutes.

[0051] In a preferred embodiment of the present invention, the curing temperature is room temperature (eg, 20° C.), and the curing humidity is 90% to 92%.

[0052] Embodiment 1

[0053] A fly ash-graphite tailings base polymer is prepared, and the preparation method comprises the following steps:

[0054] Prepare an alkali activator with a modulus of 2.0, and then prepare an alkali activator solution according to a weight ratio of 40% of the alkali activator;

[0055] Mix the calcined graphite tailings and fly ash in a weight ratio of 1:4, and then mix the cement of the same mass as the graphite tailings and fly ash; pour the prepared alkaline activator solution into the above mixed raw materials at a liquid-to-cement ratio of 0.38, first pour half of the total volume, stir evenly with a stirrer, and pour the remaining half of the alkaline activator solution during the stirring process, and the stirring time is 2 to 4 minutes. Pour the stirred slurry into a 40mm×40mm×160mm triple stainless steel mold, scrape the surface and vibrate it on a vibration table for 2 to 4 minutes, and cover it with a plastic cover; put the mold filled with the slurry into a constant temperature and humidity curing box, and demold it after curing for 24 hours to obtain a fly ash-graphite tailings base polymer test block. The microscopic morphology of the geopolymer obtained in this example is shown in Figure 5 Its microstructure characterization data is shown in Table 2.

[0056] Embodiment 2

[0057] A method for preparing fly ash-graphite tailings-graphite tailings ultrafine powder-based cement geopolymer is prepared, and the preparation method comprises the following steps:

[0058] Prepare an alkali activator with a modulus of 2.0, and then prepare an alkali activator solution according to a weight ratio of 40% of the alkali activator;

[0059] The calcined activated graphite tailings, the graphite tailings ultrafine powder obtained by the aforementioned chemical ultrafine treatment (the physical properties of the graphite tailings before and after the chemical ultrafine treatment are shown in Table 1) and fly ash are uniformly mixed in a weight ratio of 0.25:0.75:4, and then cement of the same mass as the graphite tailings, ultrafine powder and fly ash is mixed therein;

[0060] Table 1

[0061]

[0062] Pour the prepared alkaline activator solution into the mixed raw materials according to the liquid-to-gel ratio of 0.38. Pour half of the total volume first, stir evenly with a blender, and pour the remaining half of the alkaline activator solution during the stirring process. The stirring time is 2 to 4 minutes.

[0063] Pour the stirred slurry into a 40mm×40mm×160mm triple stainless steel mold, scrape the surface flat and vibrate on a vibration table for 2-4 minutes, then cover with a plastic cover;

[0064] The mold filled with the slurry was placed in a constant temperature and humidity curing box, and demoulding was performed after curing for 24 hours to obtain a fly ash-graphite tailings ultrafine powder-based polymer test block. The microscopic morphology of the geopolymer obtained in this example is shown in Figure 6 Its microstructure characterization data is shown in Table 2.

[0065] Table 2

[0066]

[0067] Embodiment 3

[0068] A method for preparing a fly ash-graphite tailings-graphite tailings ultrafine powder-based polymer is prepared, and the preparation method comprises the following steps:

[0069] Prepare an alkali activator with a modulus of 2.0, and then prepare an alkali activator solution according to a weight ratio of 40% of the alkali activator;

[0070] The same graphite tailings, ultrafine powder and fly ash as in Example 2 were mixed uniformly in a weight ratio of 0.25:0.75:4 without adding cement;

[0071] Pour the prepared alkaline activator solution into the mixed raw materials according to the liquid-to-gel ratio of 0.38. Pour half of the total volume first, stir evenly with a blender, and pour the remaining half of the alkaline activator solution during the stirring process. The stirring time is 2 to 4 minutes.

[0072] Pour the stirred slurry into a 40mm×40mm×160mm triple stainless steel mold, scrape the surface flat and vibrate on a vibration table for 2-4 minutes, then cover with a plastic cover;

[0073] The mold filled with the slurry was placed in a constant temperature and humidity curing box and demoulded after curing for 24 hours to obtain a cement slurry test block.

[0074] Comparative Example 1

[0075] A geopolymer containing only cement is prepared, the preparation method comprising the following steps:

[0076] Prepare an alkali activator with a modulus of 2.0, and then prepare an alkali activator solution according to a weight ratio of 40% of the alkali activator; the raw material is only cement of the same mass as the raw material in Example 1 or Example 2; pour the prepared alkali activator solution into the above raw materials at a liquid-to-cement ratio of 0.38, first pour half of the total volume, stir evenly with a stirrer, and pour the remaining half of the alkali activator solution during the stirring process, and the stirring time is 2 to 4 minutes. Pour the stirred slurry into a 40mm×40mm×160mm triple stainless steel mold, scrape the surface flat, vibrate on a vibration table for 2 to 4 minutes, and cover the plastic cover; put the mold containing the slurry into a constant temperature and humidity curing box, and demold it after curing for 24 hours to obtain a cement slurry test block.

[0077] Comparative Example 2

[0078] The fly ash-based polymer was prepared by adding rare earth waste residue. The overall method was similar to that of Comparative Example 1, except that:

[0079] During the preparation of the alkali activator, an appropriate amount of silicon is added, the silicon-aluminum ratio in the raw material is corrected, and the mixture is stirred evenly and left to stand for 10 minutes for use; an appropriate amount of fly ash and rare earth waste residue are weighed and placed in a stirring container, and after being fully mixed, the prepared composite alkali activator is added and stirred for 5 minutes to obtain a slurry; the molded geopolymer is placed in a constant temperature drying oven with the mold, and the curing temperature is 55°C to 85°C, and finally a fly ash-based polymer mixed with rare earth waste residue is obtained, and its microscopic morphology is shown in FIG. Figure 7 As shown. In this comparative example, when the curing temperature is 75°C, the liquid-solid ratio is 0.33, and the mass ratio of the rare earth waste residue is 5%, the compressive strength of the geopolymer is the highest, reaching 30.47MPa. It shows that under this condition, the compressive strength of the geopolymer cementitious material prepared with rare earth low-radioactivity waste residue and fly ash as raw materials is lower than that of Example 1 and Example 2. Its microstructure contains more pores and its density is lower than that of Example 1 and Example 2, which confirms the conclusion of compressive strength.

[0080] Comparative Example 3

[0081] Iron tailings, blast furnace slag and fly ash are mixed as silicon-aluminum raw materials to prepare geopolymers. The specific method includes: stimulating the reaction activity of the raw materials by mechanical grinding and alkaline activator, the mechanical grinding time is set to 60 minutes, and the specific surface area of ​​the iron tailings after grinding is 632.13m 2 / kg (i.e. 0.632m 2 / g), the specific surface area of ​​blast furnace slag after grinding is 497.32m 2 / kg (i.e. 0.497m 2 / g); the modulus of alkali activator water glass is 1.2, the dosage is 10%, and the water-cement ratio is 0.45; when the fly ash dosage is 10%, the ratio of blast furnace slag to iron tailings is 5:3, the compressive strength of the prepared geopolymer sample at 3, 7, and 28 days is 10.7, 18.9, and 32.9 MPa respectively. Its microscopic morphology is shown in Figure 8 The specific surface area of ​​the raw material obtained by grinding in this comparative example is much smaller than that of Example 2, and the microstructure of the geopolymer finally obtained is in the shape of piled wrinkles, and the density is lower than that of Example 2.

[0082] Strength performance testing

[0083] The compressive and flexural strength tests of the geopolymer test blocks prepared in Example 1, Example 2, Example 3 and Comparative Example 1 were performed at 3d, 7d and 28d using the GB / T 17671-2021 testing method. The compressive strength test results are shown in Figure 2 , flexural strength test results are shown in Figure 3 .

[0084] from Figure 2 and Figure 3It can be seen that, when fly ash and graphite tailings are used as raw materials in large proportions in Examples 1 and 2 of the present invention, the compressive strength is still equivalent to that of Comparative Example 1 which uses cement as the cementitious material. In particular, after ultrafine graphite tailings powder is further added in Example 2, its early strength even exceeds that of Comparative Example 1. In terms of flexural strength, after fly ash and graphite tailings are used as raw materials in large proportions in Examples 1 and 2 of the present invention, the early and late flexural strengths are significantly higher than those of Comparative Example 1.

Claims

1. A method for preparing a geopolymer, comprising using fly ash and graphite tailings as raw materials, wherein the weight ratio of the fly ash to the graphite tailings is 4:0.25-1; or using fly ash, graphite tailings and ultrafine graphite tailings powder as raw materials, wherein the mass ratio of the fly ash, graphite tailings and ultrafine graphite tailings powder is 4:0.25:0.75; after uniformly mixing the raw materials, adding an alkaline activator solution and stirring for 2-4 minutes, and forming and curing for 28 days to obtain a geopolymer based on solid waste.

2. The preparation method according to claim 1, characterized in that: The fly ash is spherical fly ash; further preferred is low-calcium Class F secondary fly ash, whose components are: SiO2 content 66% to 68%, Al2O3 content 17% to 18%, CaO content 4% to 6%, Fe2O3 content 4% to 4.5%, and SO3 content 0.2% to 0.3%.

3. The preparation method according to claim 1, characterized in that: The graphite tailings are calcined and activated graphite tailings; in the preferred graphite tailings, the SiO2 content is 35% to 65%, and the content ratio of SiO2 to Al2O3 is between 2 and 5.

4. The preparation method according to claim 1, characterized in that: The graphite tailings ultrafine powder is an ultrafine powder obtained by chemical ultrafine treatment of graphite tailing particles, specifically, the ultrafine powder with a microscopic morphology of spherical or cubic is obtained by grinding the calcined activated graphite tailing particles with NaOH fine powder, and then performing high-temperature roasting, grinding, low-temperature aging and hydrothermal reaction in sequence; in the graphite tailings ultrafine powder, more than 90% of the particles have a particle size of no more than 20μm; the micropore area is no less than 30m 2 / g; specific surface area not less than 19m 2 / g.

5. The preparation method according to claim 1, characterized in that: The graphite tailings ultrafine powder is prepared according to the following method: 1) mixing sodium hydroxide (NaOH) fine powder with calcined activated graphite tailing particles in a weight ratio of 0.6 to 2.0:1 and grinding them together until they are completely mixed and then roasting them at 650° C. to 750° C. for 2 h to 4 h; 2) mixing the solid treated in step 1) with sodium silicate at a weight ratio of 1:0.30-0.80 and grinding them into powder, then adding water at a solid-liquid ratio of 6-12 mL / g, first aging at 50-80° C. for 1 h-3 h, and then aging at room temperature for 12 h-16 h to obtain a precursor for a hydrothermal reaction; 3) subjecting the precursor obtained in step 2) to a hydrothermal reaction at 95° C. to 110° C. for 7 h to 9 h, followed by cooling, filtering and drying to obtain the ultrafine graphite tailings powder used in the preparation method of the present invention.

6. The preparation method according to claim 1, characterized in that: The alkaline activator solution is a water glass solution with a modulus of 1.6 to 2.2; the liquid-to-gel ratio of the added alkaline activator solution is 0.35 to 0.44, and the proportion of the alkaline activator solution in the system liquid is 20% to 50%.

7. A method for preparing a geopolymer, using fly ash, graphite tailings, ultrafine graphite tailings powder and cement as raw materials, wherein the mass ratio of fly ash, graphite tailings, ultrafine graphite tailings powder and cement is 4:0.25:0.75:5; after the raw materials are evenly mixed, an alkaline activator solution is added and stirred for 2 to 4 minutes, and after molding and curing for 28 days, a solid waste-based geopolymer is obtained.

8. The preparation method according to claim 7, characterized in that: The fly ash is spherical fly ash; further preferred is low-calcium Class F secondary fly ash, whose components are: SiO2 content 66% to 68%, Al2O3 content 17% to 18%, CaO content 4% to 6%, Fe2O3 content 4% to 4.5%, SO3 content 0.2% to 0.3%; the graphite tailings are calcined and activated graphite tailings; in the preferred graphite tailings, the SiO2 content is 35% to 65%, and the content ratio of SiO2 to Al2O3 is between 2-5.

9. The preparation method according to claim 7, characterized in that: The graphite tailings ultrafine powder is an ultrafine powder obtained by chemical ultrafine treatment of graphite tailing particles, specifically, the ultrafine powder with a microscopic morphology of spherical or cubic is obtained by grinding the calcined activated graphite tailing particles with NaOH fine powder, and then performing high-temperature roasting, grinding, low-temperature aging and hydrothermal reaction in sequence; in the graphite tailings ultrafine powder, more than 90% of the particles have a particle size of no more than 20μm; the micropore area is no less than 30m 2 / g; specific surface area not less than 19m 2 / g.

10. The preparation method according to claim 7, characterized in that: The liquid-to-gel ratio of the added alkali activator solution is 0.35-0.44 and the proportion of the alkali activator solution in the system liquid is 20%-50%.

Citation Information

Patent Citations

  • Preparation method of graphite tailing-metakaolin-based geopolymer cementing material

    CN118459132A